Downregulation of microRNA-451 in non-alcoholic steatohepatitis inhibits fatty acid-induced proinflammatory cytokine production through the AMPK/AKT pathway. (July 2015) - Hur, Wonhee; Lee, Joon Ho; Kim, Sung Woo; Kim, Jung-Hee; Bae, Si Hyun; Kim, Minhyung; Hwang, Daehee; Kim, Young Seok; Park, Taesun; Um, Soo-Jong; Song, Byoung-Joon; Yoon, Seung Kew
Highlights: Hepatic inflammation is one of the most distinguishing features of NASH. miR-451 expression was down-regulated in the inflammatory progression of NAFLD. Downregulation of miR-451 mediates the hepatic inflammation. miR-451 over-expression suppresses PA-induced proinflammatory cytokine production in steatotic cells. miR-451 expression inhibits PA- induced NF-κB activation in steatotic cells. Abstract: Mechanisms associated with the progression of non-alcoholic fatty liver disease (NAFLD) remain unclear. We attempted to identify the pattern of altered gene expression at different time points in a high fat diet (HFD)-induced NAFLD mouse model. The early up-regulated genes are mainly involved in the innate immune responses, while the late up-regulated genes represent the inflammation processes. Although recent studies have shown that microRNAs play important roles in hepatic metabolic functions, the pivotal role of microRNAs in the progression of NAFLD is not fully understood. We investigated the functions of miR-451, which was identified as a target gene in the inflammatory process in NAFLD. miR-451 expression was significantly decreased in the palmitate (PA)-exposed HepG2 cells and in liver tissues of HFD-induced non-alcoholic steatohepatitis (NASH) mice. Its decreased expressions were also observed in liver specimens of NASH patients. In vitro analysis of the effect of miR-451 on proinflammatory cytokine provided evidence for negative regulation of PA-induced interleukin (IL)-8 and tumor necrosis factor-alpha (TNF-α) production. Furthermore, miR-451 over-expression inhibited translocation of the PA-induced NF-κB p65 subunit into the nucleus. Our result showed that Cab39 is a direct target of miRNA-451 in steatotic cells. Further study showed that AMPK activated through Cab39 inhibits NF-κB transactivation induced in steatotic HepG2 cells. miR-451 over-expression in steatotic cells significantly suppressed PA-induced inflammatory cytokine. These results provide new insights into the negative regulation of miR-451 in fatty acid-induced inflammation via the AMPK/AKT pathway and demonstrate potential therapeutic applications for miR-451 in preventing the progression from simple steatosis to severely advanced liver disease.